Development of MATLAB programs for transfer matrices - Wang, Liedong (Nanyang Technological University, 2022)
In fields such as engineering, physics, and science, there are many matrices and complex number operations used in research and projects. Applying these calculations, engineers or researchers can either perform theoretical calculations prior to experimentation and then appropriately build structures to meet their needs, or they can verify the results of the implementation. There are some scientific calculators or programs that can perform simple matrix numerical operations, but it is rare to see complex matrix calculations such as ABCD matrices for cascaded transmission lines, optical constants matrix for multilayer films, Jones matrix for optical devices, and the transfer matrix method for solving 1-D Schrödinger equation.